Homogenized material properties for cross‐laminated timber. Issue 1 (17th December 2018) - Furtmüller, Thomas; Adam, Christoph; Giger, Benjamin
Abstract: In this contribution the coefficients of the elastic stiffness tensor of a generalized shell section for cross‐laminated timber (CLT) slabs are derived by application of a numerical homogenization scheme based on a repeating unit cell (RUC). In an example it is shown that a finite shell element model with those homogenized shell stiffness parameters predicts closely the modal properties of a CLT slab, thus, verifying the accuracy of the applied homogenization procedure for this type of structural members.